2022
DOI: 10.48550/arxiv.2210.02830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KnowledgeShovel: An AI-in-the-Loop Document Annotation System for Scientific Knowledge Base Construction

Abstract: Constructing a comprehensive, accurate, and useful scientific knowledge base is crucial for human researchers synthesizing scientific knowledge and for enabling AI-driven scientific discovery. However, the current process is difficult, error-prone, and laborious due to (1) the enormous amount of scientific literature available; (2) the highly-specialized scientific domains; (3) the diverse modalities of information (text, figure, table); and, (4) the silos of scientific knowledge in different publications with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To better extract and manage data, we design and impletment an AI-in-the-loop system, DeepShovel [13,14,15], where researchers collaborate with AI in extracting data efficiently from literature to build a scientific knowledge base with high data quality without the dependence of data scientists…”
Section: Multi-model Data Extraction From Paper Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…To better extract and manage data, we design and impletment an AI-in-the-loop system, DeepShovel [13,14,15], where researchers collaborate with AI in extracting data efficiently from literature to build a scientific knowledge base with high data quality without the dependence of data scientists…”
Section: Multi-model Data Extraction From Paper Contentmentioning
confidence: 99%
“…The complete work of the system including the formative study, system description, and user study can be found at [13,14,15]. DeepShovel allows users to navigate through different tabs such as Meta, Text, Table , and Map to facilitate different aspects of data extraction.…”
Section: System Designmentioning
confidence: 99%